2017
DOI: 10.4330/wjc.v9.i4.347
|View full text |Cite
|
Sign up to set email alerts
|

QT prolongation is associated with increased mortality in end stage liver disease

Abstract: AIMTo determine the prevalence of QT prolongation in a large series of end stage liver disease (ESLD) patients and its association to clinical variables and mortality.METHODSThe QT interval was measured and corrected for heart rate for each patient, with a prolonged QT cutoff defined as QT > 450 ms for males and QT > 470 ms for females. Multiple clinical variables were evaluated including sex, age, serum sodium, international normalized ratio, creatinine, total bilirubin, beta-blocker use, Model for End-Stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…A prolonged QT interval represents a common electrocardiographic finding in patients with cirrhosis and served as predictor of the increased risk of ventricular arrhythmia and/or sudden death [57]. QT prolongation has been attributed to the downregulation of β-adrenergic receptors after chronic exposure to noradrenalin [58].…”
Section: Electrophysiological Modificationsmentioning
confidence: 99%
“…A prolonged QT interval represents a common electrocardiographic finding in patients with cirrhosis and served as predictor of the increased risk of ventricular arrhythmia and/or sudden death [57]. QT prolongation has been attributed to the downregulation of β-adrenergic receptors after chronic exposure to noradrenalin [58].…”
Section: Electrophysiological Modificationsmentioning
confidence: 99%
“…Both CAN, even subclinical, and QT prolongation have been associated with increased all-cause mortality in patients with diabetes[ 7 - 9 ]. Interestingly, some studies have shown that the prolongation of QT interval in patients with cirrhosis has been associated with the severity and progression of the disease and with poorer survival in cirrhotic patients[ 10 - 13 ]. On the other hand, in other studies, even though prolonged QT was associated with more severe liver dysfunction, this has not been translated to higher mortality[ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons that AF is linked to higher mortality and morbidity are likely higher rates of stroke and acute kidney injury (AKI). Also, long QT is commonly seen in advanced liver disease and is a strong predictor of increased death[ 13 ].…”
Section: Discussionmentioning
confidence: 99%